Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa untuk Berinvestasi di Pasar Modal Syariah Melalui Platform Investasi Digital: Studi Kasus Mahasiswa Institut Pesantren Kh.Abdul Chalim Mojokerto - Zakia Darojat; Nur Dinah Fauziah; Rahma Sandhi Prahara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to determine the factors that influence the interest of KH.Abdul Chalim Islamic Boarding School students' interest in investing in the Sharia Capital Market through the Digital Investment Platform. This research is a type of qualitative research with a case study approach. This research uses primary data obtained from observations and interviews and tertiary data obtained from the student affairs bureau. The data collection techniques used are observation, interviews and documentation. The data analysis technique used is data triangulation.The results of this research are: Factors that influence student interest at the KH Islamic Boarding School. Abdul Chalim's desire to invest in the Sharia Capital Market through the Digital Investment Platform comes from internal factors including interest, desire and belief. Interest that comes from within the individual, such as applying theories learned in college, being inspired by Korean drama films and role models. Desire to hope for something that interests you, such as wanting to gain profits from investment results. Belief is an individual's belief in something that has qualities and benefits.